2014
DOI: 10.1093/nar/gku532
|View full text |Cite
|
Sign up to set email alerts
|

Physiological state co-regulates thousands of mammalian mRNA splicing events at tandem splice sites and alternative exons

Abstract: Thousands of tandem alternative splice sites (TASS) give rise to mRNA insertion/deletion variants with small size differences. Recent work has concentrated on the question of biological relevance in general, and the physiological regulation of TASS in particular. We have quantitatively studied 11 representative TASS cases in comparison to one mutually exclusive exon case and two cassette exons (CEs) using a panel of human and mouse tissues, as well as cultured cell lines. Tissues show small but significant dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 29 publications
4
20
0
Order By: Relevance
“…6 Together, three studies provided highresolution evidence that 3 0 TASS isoform ratios differ across different mammalian tissues. 6,34,38 Even though Tsai and Lin concluded that NAGNAG isoform ratios are "almost constant among tissues," their presented results do nicely fit other reports which diagnose cross-tissue differences. 34,38 Also the results from RNA-seq data support the tissue-dependent differences, with somewhat less resolution on individual TASS cases but clearly higher genome-wide coverage.…”
Section: Tass Alternative Splicing Is Regulated Though With Low Dynasupporting
confidence: 82%
See 3 more Smart Citations
“…6 Together, three studies provided highresolution evidence that 3 0 TASS isoform ratios differ across different mammalian tissues. 6,34,38 Even though Tsai and Lin concluded that NAGNAG isoform ratios are "almost constant among tissues," their presented results do nicely fit other reports which diagnose cross-tissue differences. 34,38 Also the results from RNA-seq data support the tissue-dependent differences, with somewhat less resolution on individual TASS cases but clearly higher genome-wide coverage.…”
Section: Tass Alternative Splicing Is Regulated Though With Low Dynasupporting
confidence: 82%
“…6,34,38 Even though Tsai and Lin concluded that NAGNAG isoform ratios are "almost constant among tissues," their presented results do nicely fit other reports which diagnose cross-tissue differences. 34,38 Also the results from RNA-seq data support the tissue-dependent differences, with somewhat less resolution on individual TASS cases but clearly higher genome-wide coverage. 6 Next, concerning the extent of crosstissue variation in isoform ratios, two studies are very close in their conclusion that the isoform ratios are "almost constant" or "very small" compared to tissue-specific splicing of cassette exons.…”
Section: Tass Alternative Splicing Is Regulated Though With Low Dynasupporting
confidence: 82%
See 2 more Smart Citations
“…STAT3 auto-regulates its own expression 37 , and the protocol described above may help to elucidate whether ratios of STAT3 splice variants contribute to regulating this positive feedback loop. The protocol could be used to study shifts in splice variant ratios as observed in cells at differing densities 38 or over the course of development: it is known that the STAT3 α/β ratio changes at the protein level during hematopoiesis 16 . Sundin et al found that an intronic single nucleotide polymorphism biased splicing of exon 12 in STAT3 of a patient with Job's syndrome 39 .…”
Section: Discussionmentioning
confidence: 99%